Pengaruh Motivasi Dan Kepercayaan Diri Terhadap Kinerja Majelis Gereja Hkbp Metro - Tampubolon, Tommy Martua; Ariswandy, David (Jurnal Multidisiplin Dehasen (MUDE), 2025)
The HKBP Metro Church Council has experienced significant development since its establishment, initially consisting of a small number of members who managed church activities. As the congregation grew and the complexity of tasks increased, the number of council members also rose, and they are now responsible for worship, religious activities, as well as administrative, social, and financial aspects. Although the quality of human resources has improved through training and the application of technology, low motivation and self-confidence among the members remain challenges, evidenced by a delay rate exceeding 10% each month. Efforts to enhance self-confidence through training have not been fully effective, and visits by the council to the congregation, along with education and health programs, need to be improved. Further research is needed to understand the impact of motivation and self-confidence on the performance of the council and to design interventions to improve church services. This research will be conducted at the HKBP Metro Church, chosen for its relevance to the research focus and for having a sufficient number of councils to serve as a sample. The study will take place from June to July 2024, using a descriptive quantitative approach. This type of research aims to present facts and characteristics of the population systematically and accurately. The method employed is field research with a quantitative approach, which is objective in nature. The population in this study consists of 42 members of the HKBP Metro Church Council. The researcher will include all members except themselves, resulting in a sample size of 41. This study is categorized as population research. The variables used include independent variables, namely Motivation (X1) and Self-Confidence (X2), and a dependent variable, which is Council Performance (Y), influenced by the independent variables. Based on the data analysis and hypothesis testing conducted, conclusions have been drawn regarding the factors influencing the performance of the HKBP Metro Church Council. First, the Motivation variable (X1) has an influence of 41.1% on Council Performance (Y). Second, the Self-Confidence variable (X2) also has an influence of 41.1% on Council Performance (Y). Third, both Motivation (X1) and Self-Confidence (X2) simultaneously have an influence of 57.5% on Council Performance (Y) at the HKBP Metro Church.